2018
DOI: 10.3892/etm.2018.6230
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of Mda‑7/IL‑24 and C‑myb expression in tumor tissues of patients with diffuse large B cell lymphoma

Abstract: Diffuse large B cell lymphoma (DLBCL) is the most common type of non-Hodgkin's lymphoma in adults. Mda-7/IL-24 had been identified as a differentiation inducer of B phenotype lymphoma cells. Previous studies have revealed that knockdown of C-myb also leads to the terminal differentiation of B cell lymphoma. The aim of the present study was to investigate the association between the expression of Mda-7/IL-24 and C-myb, and their prognostic significance for DLBCL patients. The tumor tissues were collected from 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…It was well accepted that IL-24 mediated cancer cell-specific death and apoptosis via multiple signaling pathways (21)(22)(23). Significantly lower IL-24 expression predicted poorer prognosis in lung adenocarcinoma (24), breast cancer (25), head and neck squamous cell carcinoma (26), and lymphoma (27,28). IL-24 high adenocarcinoma patients showed a notably higher incidence of apoptotic tumor cell death, and displayed favorable post-therapy prognosis as compared with IL-24 low patients (24).…”
Section: Discussionmentioning
confidence: 99%
“…It was well accepted that IL-24 mediated cancer cell-specific death and apoptosis via multiple signaling pathways (21)(22)(23). Significantly lower IL-24 expression predicted poorer prognosis in lung adenocarcinoma (24), breast cancer (25), head and neck squamous cell carcinoma (26), and lymphoma (27,28). IL-24 high adenocarcinoma patients showed a notably higher incidence of apoptotic tumor cell death, and displayed favorable post-therapy prognosis as compared with IL-24 low patients (24).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, tumors from patients with poor prognosis expressed lower MDA-7/IL-24 transcript levels as compared with their counterparts predicted to have good prognosis. Two recent studies analyzed MDA-7/IL-24 expression and its correlation with clinicopathological parameters and evaluated the prognostic values in hematopoietic tumors including Burkitt lymphoma and diffuse large B cell lymphoma (DLBCL) [71,72]. MDA-7/IL-24 expression was decreased in DLBCL tissues, and low expression of MDA-7/IL-24 was a predictor of poor prognosis [71].…”
Section: Clinical Correlation-mentioning
confidence: 99%
“…Two recent studies analyzed MDA-7/IL-24 expression and its correlation with clinicopathological parameters and evaluated the prognostic values in hematopoietic tumors including Burkitt lymphoma and diffuse large B cell lymphoma (DLBCL) [71,72]. MDA-7/IL-24 expression was decreased in DLBCL tissues, and low expression of MDA-7/IL-24 was a predictor of poor prognosis [71]. Similar clinical correlations were found in Burkitt lymphoma where low expression of MDA-7/ IL-24 was associated with a worse clinical condition [72].…”
Section: Clinical Correlation-mentioning
confidence: 99%
“…In our study, Bone marrow is involved in 28.1% of cases and this is close Kim et al [23] & Park et al [26] which was 15.2% and 17.1% respectively. However, in the study by, Ma et al [27] higher proportion of Bone marrow involvement is found and represented 29.1% of cases, and this might be due to difference in sensitivity of laboratory or imaging method used to detect bone marrow involvement. The frequency of HCV infection in our patients was 18.8% of cases and this is near to Haggag et al [28] , which was 26.5% .However, In the study done by Dlouhy et al [29] carried out in spain, only 9.7% of DLBCL patients were found to have HCV infection and this might be attributed to difference in sample size and the very high prevalence of HCV infection among Egyptians.…”
Section: Discussionmentioning
confidence: 87%